Flowering and Fruiting Phenology of Kecipir (Psophocarpus tetragonilobus (L.) DC.) - Anggun Yuniar; Pinta Murni; Erick Sanjaya (Jurnal Inovasi Pendidikan dan Sains, 2025)
Winged bean (Psophocarpus tetragonolobus (L.) DC.) is a plant with high potential as a nutritious food source. Information on the flowering and fruiting phenology of winged bean is the main focus of this study, which aims to observe and analyze each phase of flower and fruit development as well as environmental factors. The study was conducted in Pandan Lagan Village, Geragai District, East Tanjung Jabung Regency, Jambi, from September 2024 to January 2025, using a descriptive method with qualitative and quantitative approaches. The study population included all winged bean plants planted at the study site, while three winged bean plants were sampled. Each plant was observed for five flower buds, resulting in a total sample of 15 flower buds. Observations were made on the flower and fruit development phases, starting from the initiation phase of flower bud formation, until ripe fruit, and environmental factors. Observations were carried out every day, namely at 08.00–10.00 WIB. The results of the study showed that the winged bean flowering phase lasted for 22 days, the initiation to anthesis phase lasted for 20 days, followed by a two-day post-anthesis phase. Meanwhile, the fertilization process from fruit initiation to maturity lasted for 13 days. Environmental factors included an average temperature of 26.04°C, air humidity of 40.69%, light intensity of 4,435.46 lux, and rainfall of 9.68 mm. These findings are expected to provide data information that can be used as a crucial basis for consideration in planning winged bean cultivation in the region